Clinicopathologic Significance and Immunogenomic Analysis of Programmed Death-Ligand 1 (PD-L1) and Programmed Death 1 (PD-1) Expression in Thymic Epithelial Tumors - Song, Joon Seon; Kim, Deokhoon; Kwon, Ji Hyun; Kim, Hyeong Ryul; Choi, Chang-Min; Jang, Se Jin (Frontiers in Oncology, 2019)
Objectives: Thymic epithelial tumors (TETs) are rare malignant tumors that exhibit heterogeneous histology and clinical behavior. As immune check point inhibitors, drugs targeting anti-programmed cell death protein 1 (PD-1) and programmed death-ligand 1 (PD-L1) have shown remarkable results against many cancers; thus, the importance of PD-1/PD-L1 immunohistochemistry as a predictive or prognostic biomarker has grown. However, limited data on PD-L1 and PD-1 expression in TETs have been reported; moreover, these results have been variable. Here, we examined the expression of PD-1/PD-L1 proteins in TETs and analyzed the clinicopathologic significance of this expression. Patients and Methods: A tissue microarray was constructed using 368 samples of TETs, each in triplicate. Immunohistochemistry for PD-L1 (SP263 assay) and PD-1 in TETs and CD8 in thymic carcinoma (TC) was performed; next, correlations with clinicopathologic characteristics were analyzed. PD-L1high was designated as 50% of tumor proportion score; PD-1high and CD8high were defined as 5% and 1% of tumoral immune cells, respectively. Results: The cohort consisted of 308 patients with thymomas and 60 patients with TC. PD-L1 positivity was identified in 90.6% (328/362, 1%) of TETs, PD-1 expression of intra-/peritumoral T cells was identified in 53.6% (194/362) of TETs and CD8 positivity was identified in 11 % (7/60, 1%) of TC. Of the 362patients, 141 (39.0%) exhibited high PD-L1 expression (PD-L1high). The PD-L1high thymoma group was correlated with high Masaoka-Koga stage (p < 0.001), type B3 histology (p < 0.001), and myasthenia gravis (p < 0.001). This group exhibited poor overall survival (OS, p = 0.003, log-rank) and worse disease-free survival (DFS, p = 0.042, log-rank). No survival differences were detected between PD-L1high and PD-L1low groups in TC. Additionally, there was no correlation between PD-1 expression and survival in patients with TETs. Multivariate analysis revealed that PD-L1high expression was an independent poor prognostic factor (p = 0.047, HR 2.087, 95% CI, 1.009-4.318) in thymomas. Conclusions: To our knowledge, this is the largest study on TETs published in English literature. This study provides useful information regarding the prognosis of and potential therapeutic options for patients with TETs.